Case Study on Structural Design Implementation for Architecturally Complex Reinforced Concrete Buildings - Sugiarto; Haikal Nur Rachmanrachim Achaqie (Civil Engineering Science and Technology, 2026)
The growing need for architecturally distinctive buildings with complex shapes poses a challenge to structural engineers in reinforced concrete construction. This paper examines the effectiveness of structural design implementation in architecturally complex reinforced concrete buildings through early interdisciplinary collaboration and analytical techniques. A single-case study method was adopted, and the 45-story Meru Tower in Jakarta, with a twisted façade and irregular floor plans, was selected as the case study. Data collection was done using semi-structured interviews with eight key participants and document analysis of structural design calculations, finite element analysis results, and BIM coordination reports. The results show that early co-location of structural engineers with architects, assisted by structured BIM procedures, facilitated real-time geometric feasibility checks and avoided costly design conflicts at a later stage. Technical problems related to torsional irregularities and stress concentrations were addressed through response spectrum analysis, nonlinear time-history analysis, outrigger walls, and post-tensioned transfer girders. Quantitative validation confirmed that all performance criteria were met, including a 0.18% drift ratio, a 1.15 torsional ratio, and a maximum stress of 16.2 MPa, with a 9% reduction in concrete volume. This paper presents a three-phase approach derived from the Meru Tower case, offering practical insights for structural design implementation in architecturally complex concrete buildings. However, further validation across multiple cases is required.